Efficient Non-Conservative Realization of Dynamic Scaling-Based Output-Feedback Controllers via a Matrix Pencil Approach. Issue 2 (2020) - Krishnamurthy, P.; Khorrami, F.
Abstract: A general matrix pencil based approach is developed for efficient non-conservative realization of dual dynamic high-gain scaling based control designs. A general class of uncertain feedforward-like nonlinear systems is considered and it is shown that the output-feedback control design procedure can be cast into a set of matrix pencil based sub-problems that capture the detailed system structure, state dependence structure of uncertain terms, and the precise roles of the design freedoms in the context of the detailed structure of the Lyapunov inequalities. The design freedoms in the dynamic high-gain scaling based design are extracted in terms of generalized eigenvalues of the formulated matrix pencil structures. It is seen that the proposed matrix pencil based approach greatly reduces design conservatism and algebraic complexity compared to prior results on dynamic high-gain scaling based control designs.